2016
DOI: 10.1039/c5fd00234f
|View full text |Cite
|
Sign up to set email alerts
|

Molten salt CO2capture and electro-transformation (MSCC-ET) into capacitive carbon at medium temperature: effect of the electrolyte composition

Abstract: Electrochemical transformation of CO2 into functional materials or fuels (i.e., carbon, CO) in high temperature molten salts has been demonstrated as a promising way of carbon capture, utilisation and storage (CCUS) in recent years. In a view of continuous operation, the electrolysis process should match very well with the CO2 absorption kinetics. At the same time, in consideration of the energy efficiency, a molten salt electrochemical cell running at lower temperature is more beneficial to a process powered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 49 publications
0
42
0
Order By: Relevance
“…Consequently, molten carbonate electrolysis cells could be more competitive than other conversion technologies such as hydrogenation and electrochemical reduction in chlorides or ionic liquids. 8 Several studies [9][10][11][12] have been carried out on CO 2 reduction but its specific mechanism in molten carbonate is not fully justified yet. It has been suggested that CO 2 can be reduced indirectly through the reduction of carbonates and their regeneration by absorption of CO 2 .…”
mentioning
confidence: 99%
“…Consequently, molten carbonate electrolysis cells could be more competitive than other conversion technologies such as hydrogenation and electrochemical reduction in chlorides or ionic liquids. 8 Several studies [9][10][11][12] have been carried out on CO 2 reduction but its specific mechanism in molten carbonate is not fully justified yet. It has been suggested that CO 2 can be reduced indirectly through the reduction of carbonates and their regeneration by absorption of CO 2 .…”
mentioning
confidence: 99%
“…2 a), providing evidence for the presence of reaction (1) . Deng et al [2,17] observed mass gain when CO 2 was injected into the Li 2 O-containing molten salts ( Fig. 2 b), indicating that CO 2 can be captured by reaction (2) .…”
Section: Understanding Of Co 2 Capture Processmentioning
confidence: 92%
“…Both reaction (2) and (3) contribute to the CO 2 capture, however, understanding the main contributing factor is beneficial to maximize the capture capacity of molten salts. Deng et al [2,17] compared the amounts of absorbed CO 2 in carbonate molten salts containing different Li 2 O concentrations. As shown in Fig.…”
Section: Understanding Of Co 2 Capture Processmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 With the aid of eutectic salts electrolyte, CO 2 can be captured and subsequently converted into carbon monoxide (CO), 17 solid carbon 18,19 and even valuable chemicals of carbon nanobers (CNFs) or their hollow form of carbon nanotubes (CNTs) 20,21 that are widely applied in the manufacture of reinforced composites due to outstanding mechanical properties. Presently, carbonates, especially alkali carbonates of Li 2 CO 3 , Na 2 CO 3 and K 2 CO 3 , are widely recognised as the optimum choice for CO 2 capture and conversion, but to the best of our knowledge, rare work is dedicated to investigate the effect of carbonates composition on carbon production.…”
Section: Introductionmentioning
confidence: 99%